Arnett’s soft tissue norms in north western Himalayan population: a cephalometric study - Mahadevan, Nithya; Sood, Sankalp; Mahajan, Monika; Negi, Susheel; Negi, K. S. (International Journal Of Community Medicine And Public Health, 2024)
Background: This study was conducted to establish soft tissue cephalometric norms and compare males and females of north western Himalayan range population with that of soft tissue Arnett’s norms. Methods: The study group comprised of 110 subjects (51 females and 59 males) within age 18-25 years, having class I molar relation with well-balanced faces. The null hypothesis was there will be no statistically significant difference in the soft tissue parameters between the groups. Cephalograms were manually traced and the mean values of various parameters were compared with Arnett’s norms of Caucasian population as well as between males and females of the study group. Results: The overjet, overbite, lip thickness, facial length, maxillary projection and mandibular projection were decreased in the study group when compared to the controls. Statistically significant differences were found in various parameters between males and females of the study group as compared to the control group. Males had increased overjet, increased lower facial height, retrusive maxilla, procumbent lips than females. Conclusions: This study concluded that the norms of Arnett’s Caucasian population cannot be applied to the population of other geographic regions.